(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of management skills and the extent of school heads performance of public secondary schools. This study employed non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. One hundred twenty (120) public secondary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the extent of management skills was extensive while the extent of school heads performance of public secondary schools was also extensive. Moreover, the overall results disclosed that indicators for the management skills have a strong positive correlation to the school heads performance of public secondary schools. Further, results from the regression analysis revealed that the following have a strong influence of management skills on school heads performance of public secondary schools: Leadership, Communication, and Organization. It was suggested that the Department of Education should develop a training/enhancement program that would develop the management skills of secondary school principals as they are school and community leaders in the 21st century. It was also recommended that the school heads should upgrade their management skills among secondary school heads should be continuously enhanced through attending seminars, training, and graduate studies as well as postgraduate courses.